Left Ventricular Thrombus in Old Myocardial Infarction - Abdul Alim Rahimi; Akmal Mufriadi Hanif; Taufik Rizkian Asir (HM Publisher, 2022)
Background. Left ventricular thrombus is a major risk factor for systemic thromboembolism, a complication of acute and chronic myocardial infarction. The high incidence of left ventricular thrombus in untreated acute myocardial infarction patients can be described in the pre-thrombolytic era. Left ventricular thrombus occurred in 7-46% of cases, especially in anterior or apical myocardial infarction. Case presentation. A 57-year-old man is reported with complaints of shortness of breath and a history of chest pain typical of angina, hypertension, diabetes mellitus, and smoking. On electrocardiographic examination, infrequent premature ventricular contraction and anterior extensive old myocardial infarction were found. Transthoracic echocardiography examination revealed protuberant thrombi at the apex of the left ventricle with a size of 14 x 15 mm, left ventricular ejection fraction of 20%, and akinetic at extensive anterior, anterior, anterolateral, broad apical, inferoseptal, and inferior segments. Conclusion. Untreated acute myocardial infarction has a high risk of developing left ventricular thrombus. Intravenous unfractional heparin and VKA in left ventricular thrombus patients with an increased risk of embolism respond well.